Africa in World Politics : Constructing Political and Economic Order - W. Harbeson, Donald Ro, John (Boulder, CO : Westview Press, 2017)
"The sixth edition of Africa in World Politics focuses on challenges African states face in constructing viable political economies in contexts both of familiar domestic challenges and an unprecedented mix of engagements, opportunities, and threats emanating from a turbulent and rapidly changing international order. This text, including new chapters on Nigeria and the influence of party politics on economic development, remains an invaluable resource for students of African politics seeking to navigate the continent's complex political and economic landscapes. Revised chapters consider both the extent and the limits of continued healthy growth rates in many countries; the impacts of investments by China and other BRICS countries; plateaus and some reversals in progress on human rights and democratization; dimensions of chronic state weakness deepened by insurgencies, including some that are connected to Al Qaeda and the Islamic State; and peacebuilding efforts struggling to uphold responsible sovereignty in the Sudans, the Great Lakes region, and elsewhere."--Provided by publisher.
Constructing political and economic order / John W. Harbeson -- The heritage of colonialism / Crawford Young -- Reflections on Arica's rocky love-hate relationship with international capital / Todd Moss -- Entrepreneurial governance and the expansion of public investment funds in Africa / M. Anne Pitcher -- The sad story of "Africa rising" and of the continent's romance with the BRICs / Ian Taylor -- In pursuit of autonomy : civil society and the state in Africa / Aili Mari Tripp -- Democracy and the state in Sub-Saharan Africa / John W. Harbeson -- The international factor in African warfare / William Reno -- Sudan and South Sudan : the tragic denouement of the comprehensive peace agreement / Princeton N. Lyman -- Instability in the Great Lakes region / Filip Reyntjen -- Boko Haram and Nigeria state weakness / John Campbell -- The diplomacy of African conflicts / I. William Zartman -- Bilateral vs. multilateral peacebuilding in Africa / Carrie Manning and Louis-Alexandre Berg -- The African Union's peace and security architecture -- from aspiration to operationalization / Ulf Engel -- Reconciling sovereignty with responsibility : a basis for international humanitarian action / Francis M. Deng.
Includes bibliographical references and index.
Keywords: Study skills; Africa -- Study and teaching; Africa